Closed doors, open minds : British Jewry's secret disputations - Persoff, Meir (Academic Studies Press, 2018)
For some twenty years from the late 1960s, and thereafter following a brief pause, representatives of British Jewry's religious orientations held closed-door meetings at the Chief Rabbi's residence in attempts to bridge their communal and halachic differences. This volume explores their often fiery disputations, secret until now.